2015
DOI: 10.4172/2376-0389.1000160
|View full text |Cite
|
Sign up to set email alerts
|

The Pathology of the Internal Jugular Vein Wall in Multiple Sclerosis

Abstract: In the last years it has been described a condition named Chronic Cerebrospinal Venous Insufficiency (CCSVI), frequently but not exclusively associated to Multiple Sclerosis (MS), which generated a strong scientific controversy about the epidemiological prevalence and the possible role in the complex, multi-factorial MS ethio-pathogenesis.However, CCSVI description also stimulated a considerable research activity on the extracranial veins. Among the fields of interest, the pathology of the Internal Jugular Vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…When hypoplasia, external compression, and/or intraluminal defects (eg, defective valve and/or septum) of the internal jugular and/or azygos vein are diagnosed, the condition is known as chronic cerebrospinal venous insufficiency (CCSVI). [1][2][3][4][5][6][7][8][9] The reported prevalence of CCSVI in multiple sclerosis (MS) patients and in healthy controls is highly heterogeneous in the literature, as reported by 2 metaanalyses. 10,11 This has generated considerable scientific controversy about the association between MS and CCSVI and therefore about the role of venous balloon angioplasty in improving symptoms and/or the natural history of MS. 12 However, National Institute for Health and Care Excellence (NICE) guidance encouraged further research in the form of robust randomized controlled trials (RCT).…”
Section: Introductionmentioning
confidence: 99%
“…When hypoplasia, external compression, and/or intraluminal defects (eg, defective valve and/or septum) of the internal jugular and/or azygos vein are diagnosed, the condition is known as chronic cerebrospinal venous insufficiency (CCSVI). [1][2][3][4][5][6][7][8][9] The reported prevalence of CCSVI in multiple sclerosis (MS) patients and in healthy controls is highly heterogeneous in the literature, as reported by 2 metaanalyses. 10,11 This has generated considerable scientific controversy about the association between MS and CCSVI and therefore about the role of venous balloon angioplasty in improving symptoms and/or the natural history of MS. 12 However, National Institute for Health and Care Excellence (NICE) guidance encouraged further research in the form of robust randomized controlled trials (RCT).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in the adventitia layer the presence of calcifications arranged around the vena venarum has been found. Pedriali and Zamboni believe that published evidence clearly shows the presence of abnormalities in the walls of the IJVs in MS patients [6]. Current studies do not clarify the origin of the pathology of the IJV in MS patients.…”
Section: Dear Editormentioning
confidence: 82%
“…This fact sharply contrasts with the finding of significant intraluminal (septa, webs, membranes, fixed and rudimental valves, or wall stenosis) or valvular (tricuspid valves, enlarged and malposition valve leaflets, small accessory valve leaflets) abnormalities during post-mortem examinations or surgical procedures. [42][43][44] These defective valves reduce the normal venous outflow from the brain as proven with different methodologies for flow assessment. [45][46][47] Beyond the deeply held convictions of individual researchers, the heterogeneity of Doppler studies can be reduced to three variables: the participant observed, the measuring instrument and procedure, and the observer.…”
Section: Discussionmentioning
confidence: 99%